High dose Bacillus Calmette-Guerin (BCG) for urothelial carcinoma is trickier than expected - Siddiqui, Mohammad R.; Agarwal, Piyush K. (Translational Cancer Research, 2017)
Intravesical instillation of Bacillus Clamette-Guerin (BCG) is the first line adjuvant therpay to transuretheral resection of bladder tumor (TURBT) for patients with intermediateand high-risk non-muslce invasive bladder cancer (NMIBC) lesions (1). Its effectiveness, however, comes at a cost of complications, with up to 91% of patients developing some type of irritative local symptoms (1). Additionally, about 10– 20% of responders and 66% of non-responders eventually progress to muscle-invasive disease, leaving them with an invasive option of cystoprostatectomy (2).